2022
DOI: 10.3390/catal12030296
|View full text |Cite
|
Sign up to set email alerts
|

β-Arsenene Monolayer: A Promising Electrocatalyst for Anodic Chlorine Evolution Reaction

Abstract: Materials innovation plays an essential role to address the increasing demands of gaseous chlorine from anodic chlorine evolution reaction (CER) in chlor-alkali electrolysis. In this study, two-dimensional (2D) semiconducting group-VA monolayers were theoretically screened for the electrochemical CER by means of the density functional theory (DFT) method. Our results reveal the monolayered β-arsenene has the ultralow thermodynamic overpotential of 0.068 V for CER, which is close to that of the commercial Ru/Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Except that the catalytic ability of gallenene, selenene, and tellurene has not been reported yet, other Xenes can catalyze energy generation reactions and other applications. 80 , 88 , 89 , 92 , 93 , 97 , 102 , 105 , 106 , 107 , 108 , 112 , 117 For example, Cao et al. prepared an atomic thin layer of bismuthene with an average thickness of 1.28–1.45 nm.…”
Section: Properties and Interactions Of Xenes And Hydrogelsmentioning
confidence: 99%
“…Except that the catalytic ability of gallenene, selenene, and tellurene has not been reported yet, other Xenes can catalyze energy generation reactions and other applications. 80 , 88 , 89 , 92 , 93 , 97 , 102 , 105 , 106 , 107 , 108 , 112 , 117 For example, Cao et al. prepared an atomic thin layer of bismuthene with an average thickness of 1.28–1.45 nm.…”
Section: Properties and Interactions Of Xenes And Hydrogelsmentioning
confidence: 99%
“…It is theoretically indicated that ClO * serves as the precursor for Cl 2 evolution over DSAs, implying the reasonable activity for OER. , Lim et al reported that the atomically dispersed Pt–N 4 sites doped on a carbon nanotube can catalyze the CER with excellent activity and selectivity via the Cl adsorbate instead of ClO. , This new single-atom catalyst, for the first time, breaks the scaling relationship caused by the concurrent chlorine and oxygen evolution over precious DSAs. Our recent work suggested that NiN 4 complex-embedded graphene and β-arsenene monolayer are promising candidates for electrocatalytic CER, yet the investigations of electrocatalysts beyond DSAs for the CER are still rare. , To date, the metal–organic frameworks (MOFs), a class of materials composed of metal nodes and organic linkers, have been demonstrated to be promising for a variety of electrocatalytic reactions because of their unique properties originated from specific morphologies, for example, high surface area, large pore volume, and excellent chemical stability. , Zhao et al reported that the ultrathin MOF nanosheets can boost the OER in alkaline media with a very low overpotential . The conductive two-dimensional (2D) Ni 3 (HITP) 2 (HITP = 2,3,6,7,10,11-hexaiminotriphenylene) was first used for electrocatalytic oxygen reduction reactions in the alkaline media .…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work suggested that NiN 4 complex-embedded graphene and β-arsenene monolayer are promising candidates for electrocatalytic CER, yet the investigations of electrocatalysts beyond DSAs for the CER are still rare. 16,17 To date, the metal−organic frameworks (MOFs), a class of materials composed of metal nodes and organic linkers, have been demonstrated to be promising for a variety of electrocatalytic reactions because of their unique properties originated from specific morphologies, for example, high surface area, large pore volume, and excellent chemical stability. 18,19 Zhao et al reported that the ultrathin MOF nanosheets can boost the OER in alkaline media with a very low overpotential.…”
Section: Introductionmentioning
confidence: 99%